Penggunaan Metode Naive Bayes Classifier untuk Mengevaluasi Kinerja Akademik Mahasiswa di Perguruan Tinggi - Novitalia, Novitalia; Mawasgenti, Putri Dinanti; Apriani, Tina; S., Ahmad Prayogi; Saifudin, Aries (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Inaccuracy in selecting faculties at universities is one of the constraints experienced by students which affect academic values or student performance which affects the accuracy of student graduation, in developing a performance it is necessary to know the individual talents of the students, this is the background of the application The Naive Bayes Classifier (NBC) Algorithm method in admitting new students to find out the talents and interests of students, with the NBC method it is expected that there will be an increase in the activity of students in higher education. The research that we do focuses on evaluating the success of administering a department at a university. Our research focuses on evaluating the success of administering a department at a university using the Naive Bayes Classifier (NBC) algorithm. Because the success of student academic performance is very dependent on the level of student ability to develop the knowledge they have. So that to evaluate the performance of students, a method is needed, namely the Naive Bayes Classifier (NBC) algorithm to analyze the level of student performance. The results of this study will show which are very influential on the provisions of a classification of a student's academic performance. The results can be based on the Achievement Index (IP) so that the results obtained by the method used can be used as evaluation material for the university or related students.